The effect of introverted and extroverted architecture on security as perceived by dwellers in Iran - Rezania, Majid (2016)
The typology of architecture is a consequence of the culture and attitude of the members of a particular community toward the concept of the ideal habitat. The culture and attitude of the people are the result of the historical background of the dwellers of a pmiicular region. The case of Isfahan and Rasht show that the occurrence of numerou wars in a region has influenced on the lifestyle and attitude of people of that region towards a habitat that can fulfill their afety need which itself affects the type of the house that is built. This research aims at investigating the effect of historical wars and architectural response in the course of history on habitants ' culture in the central and northe1n parts of Iran citie of Isfahan and Rasht. It also seeks to analyze its role on the creation of introverted and extroverted type and its influence on the final construction cost. Accordingly, a mixed method research approach (combination of quantitative and qualitati e re earch techniques) using a survey-based tnethod and interview wa en1ployed in order to collect the relevant data from the re pondents of the study.